HUBUNGAN RIWAYAT PEMBERIAN ASI DENGAN KEJADIAN STUNTING PADA ANAK BALITA (USIA 3-5 TAHUN) DI KABUPATEN TAPANULI UTARA TAHUN 2016 - Simbolon, Juana Linda; Nainggolan, Dimpu Rismawaty; Sianturi, Elly (JURNAL HEALTH REPRODUCTIVE, 2017)
Introduction : Toddler age is a period of rapid growth and development so it needs to get attention as well as age groups that are vulnerable to malnutrition.There are 162 million short toddlers in Indonesia, if the continuing trend without effort is estimated to be 127 million in 2025. Stunting is welfare indicator, education and society income. Fulfilling nutrients and monitoring health during pregnancy, the exclusive breast feeding up to age of 6 months from birth as well as feeding as a companion of breast milk that has sufficient and quality can break the chain of stunting cause.Aim : this study aims to know the the history description of breast feeding with the incidence of stunting against toddlers at the age of 3-5 years in North Tapanuli Regency.Method : type of observational research with design cross sectional. The number of sample in this research is 309 children. Data analyze using chi square with CI 95% and the level of meaning is p<0.05.Result :as many 76 children (24,6%) are stunted and 13 children (9,2%) severe stunting (4,2%) or one of three quarter one from 3-4 children short stunting or very short. Short male (13, 13%) more than female (11,3%). The breastfeeding history the lower prevalence of stunting 19, 3%) and severe stunting 5,7%)Conclusion :there is a significant relationship between the breastfeeding history and the incidence of stunting (p=0,002 CI 95%)